Evaluation of the Hydrogeological Conditions of the Unconfined Aquifer in the Coastal Plain of AL-Huseen Basin - الأسعد علي; احمد محمود (Latakia University Journal -Engineering Sciences Series, 2022)
Demand for water resources has increased generally due to economic development. To meet this increasing demand, water resources must be protected from contamination and depletion. The objective of this study was to evaluate groundwater resources of unconfined aquifer in the region extending between Marqia and Al-Huseen rivers. Using a monitoring network consisting of 34 wells, water table depth measurements were recorded at least once a month. Changes in groundwater levels were then analyzed in relation to precipitation. Results show that groundwater is located close to the surface of the earth with levels quickly responding to feeding from rainwater infiltration. This, in turn, makes it vulnerable to contamination, thus threatening the viability and sustainability of these resources.